Public financial management systems Fiji key elements from a financial management perspective. (Metro Manila, Philippines Asian Development Bank, 2017)
Fijis financial reforms were disrupted by the coup of 2000. Since then, Fiji has initiated more targeted reforms. This report, for which work commenced in January 2016, documents the countrys financial management systems covering budgeting, funds flow, accounting and reporting, and auditing systems. It provides insights into Fijis internal control systems, staffing resource capacity, and information technology structure. The intent is to give project teams and consultants a better understanding of the countrys financial management systems in order to improve project preparation. Find out how high quality financial management assessments support projects by identifying key risks and enabling the implementation of appropriate actions and reforms to mitigate those risks.
Keywords: Finance -- Fiji; Fiscal policy -- Fiji; Electronic books